The Authority of Islamic Legal Fatwa: An Analytical Study of al-Qarāfī's Perspectives - Suraji (Indonesian Academy of Social and Religious Research (IASRR), 2025)
The tradition of madhhabs has been essential in shaping Islamic law, where the authority to issue fatwas guides Muslim communities and resolves legal issues. A crucial question concerns who legitimately holds this authority. This study examines the classical scholar al-Qarāfī's (626–684 AH/1228–1285 CE) contributions to fatwa authority, highlighting his flexible, integrative approach amid evolving legal needs. Using critical literature review and textual analysis, including al-Qarāfī's al-Furūq, the study explores the qualifications and limits of muftī and mujtahids, situating his views within historical debates on legal pluralism and madhhab adherence. Al-Qarāfī distinguishes two fatwa methodologies: qaulī (following authoritative madhhab opinions) and manhajī (employing ijtihad to derive new rulings). He permits qualified non-mujtahids (muqallids) to issue fatwas under certain conditions and classifies knowledge seekers (ṭālib al-‘ilm) into competency levels to define fatwa authority boundaries. His integrative model balances madhhab fidelity with flexibility, addressing tensions between orthodoxy and new legal realities. Al-Qarāfī's approach supports adaptive jurisprudence, recommending pluralism and methodological flexibility to meet modern Islamic law's complexities while preserving fatwa legitimacy.